Uji Mutu Perkecambahan Benih Gandum (Triticum aestivum L.) Beberapa Genotipe - Hondro, Alexandre Meziwasokhi; Banjarnahor, Dina Rotua Valentina; Kurnia, Theresa Dwi; Zendrato, Yuniel Melvanolo (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to evaluate and compare the germination quality of wheat seeds (Triticum aestivum L.) from several genotypes in order to identify the genotype with the best germination power and vigor. The research was carried out at the Seed Technology Laboratory, Faculty of Agriculture and Business, Satya Wacana Christian University using a Group Random Design (RAK) with three replicates. Data that did not meet the assumptions of normality and homogeneity were analyzed using the non-parametric Kruskal–Wallis test and followed by the Dunn–Bonferroni test at the level of 5%. The observation parameters were grouped into germination power parameters (germination power and growth sufficiency), vigor parameters (growth speed and wet and dry weight of sprouts), and early germination growth parameters (shoot and root length and number of leaves and roots). The results showed that the genotype had a real effect on the physiological quality of wheat seeds, where the Guri 2 genotype showed the best performance with high germination power and vigor and better root growth compared to other genotypes, while the Nias genotype also showed strong vigor and good germination quality, while the Guri 4 genotype had the lowest physiological quality of seeds with low germination power and vigor. These findings confirm the importance of the role of genetic variation in determining the physiological quality of wheat seeds, so that the Guri 2 and Nias genotypes have the potential to be used as superior genetic sources in wheat breeding programs as well as as the basis for the development and production of quality seeds to support the improvement of wheat adaptation and productivity in Indonesia.